EFEKTIFITAS KINERJA SIMPANG TAK BERSINYAL BUNDARAN KELAPA GADING DENGAN SIMPANG BERSINYAL - Setiono, Bagus; Putra, Fisika Prasetyo; Abriantoro, Adji Putra (Jurnal Kajian Teknik Sipil, 2022)
The Kelapa Gading roundabout junction, North Jakarta is one of the unsignalized intersections with the roundabout. Traffic conditions that have a density in every arm, trigger traffic jams during rush hours. In this study, an analysis of the performance of the Kelapa Gading roundabout will be presented.Primary data includes geometric, environmental conditions, traffic flow and location maps. While secondary data includes population and vehicle growth in DKI Jakarta Province. The research method uses the formula contained in the 1997 MKJI and modeling using the Vissim Student Version softwareAfter evaluating the performance of the roundabout, it is found that the capacity, degree of saturation, delays and opportunities for queuing roundabouts. If the degree of saturation DS>0.75 in one or several parts of the road can be changed to a signalized intersection.                Key words: Kelapa Gading Roundabout, Signalized intersection, MKJI,